Registros Contables de la Junta Provincial de la Cruz Roja de Los Ríos - Piza Jara, Gabriel Vicente (2017)
Clinical laboratories of low complexity are governed by the Organic Law of Health under the treatment of Establishments that provide Indirect Support Service; this law in its Agreement-2016-No. 0079 article 1 paragraph 3 indicates that establishments providing indirect support services are those in which individual units are designed, adapted or manufactured for each patient based on prescription and medical indication; and those in which activities are performed that do not require surgical interventions or prescription medications. Within this group is registered the Provincial Board Of The Red Cross Of The Rivers. In addition, the law and agreement mentioned in article 7 above d) cites that it is an obligation of the responsible of the establishment to ensure that it has the documentation that enables its operation, according to the services it provides and activity or activities that it develop. The institution is not for profit, was created initially for the purpose of carrying out missionary activities with the help of volunteers, but, given the need of the community provides the same clinical laboratory service for which it earns income to self-sustain and continue with its normal operation.